The distribution of pitch patterns and communicative types in speech chunks preceding pauses and gaps - Yanushevskaya, Irena; Ní Chasaide, Ailbhe; De Looze, Céline; Kane, John (My University, 2014)
As part of a broader study of voice prosody in speech communication, this paper looks at intonation in turn-taking. It examines the distribution of pitch patterns and communicative types in the interpausal units (IPUs) preceding pause or gap silences extracted from a corpus of spontaneous speech of Irish English. IPUs preceding speaker change (‘Gaps’) and IPUs preceding silence where the same speaker continues talking (‘Pauses’) were selected in the course of automatic extraction of pause/gap silences in dyadic dialogue interactions. A listening test was conducted to establish ‘human predictable’ pause/gap data sets which were subsequently manually annotated in terms of pitch patterns and communicative types. Overall, the Gaps and Pauses subsets show differentiation in terms of both their communicative types and pitch tunes. De- claratives and Questions are mainly found in Gaps, whereas in Pauses we mainly find Hesitations and Incomplete Declaratives. Gaps are generally characterised by falling or rising pitch patterns, whereas in Pauses a large proportion of speech samples are realised with level pitch. Classification experiments reveal discrimination of pauses and gaps for both prosodic and functional annotation labels. Follow-up work aims to relate intonational characteristics of turn taking with voice quality and temporal dynamics, to provide a holistic view of the processes involved.
Speech Prosody 7
Keywords: Dialogue speech; Pause; Gap; Intonation; Communicative type